SYNTHESIS AND CHARACTERIZATION OF COPPER(II) COMPLEX WITH 2,6-DIACETYLPYRIDINE-BIS(PHENYLHYDRAZONE) - Belošević, Svetlana; Radanović, Mirjana; Rodić, Marko; Leovac, Vukadin (Bulletin of Natural Sciences Research, 2021)
The syntheses, physicochemical and structural properties of the novel Cu(II) complex with 2,6-diacetylpyridine bis(phenylhydrazone) (L), of the formula [CuL2]Br2 are presented. In the reaction of warm MeOH solutions of the ligand, 2,6-diacetylpyridine bis(phenylhydrazone) and CuBr2 in molar ratio 2:1 resulted in formation of black single crystals of the bis(ligand) complex. This is the first Cu(II) complex with this ligand that is characterized by SC-XRD. Two ligand molecules are coordinated in the usual tridentate mode, via nitrogen atoms of the pyridine ring, and two azomethine nitrogen atoms, forming distorted octahedral environments of the metal ion.